The illusion of inclusion: contextual behavioral science and the Black community - Faber, Sonya C.; Metzger, Isha W.; La Torre, Joseph; Fisher, Carsten; Williams, Monnica T. (Frontiers in Psychology, 2023)
Anti-racism approaches require an honest examination of cause, impact, and committed action to change, despite discomfort and without experiential avoidance. While contextual behavioral science (CBS) and third wave cognitive-behavioral modalities demonstrate efficacy among samples composed of primarily White individuals, data regarding their efficacy with people of color, and Black Americans in particular, is lacking. It is important to consider the possible effects of racial stress and trauma on Black clients, and to tailor approaches and techniques grounded in CBS accordingly. We describe how CBS has not done enough to address the needs of Black American communities, using Acceptance and Commitment Therapy (ACT) and Functional Analytic Psychotherapy (FAP) as examples. We also provide examples at the level of research representation, organizational practices, and personal experiences to illuminate covert racist policy tools that maintain inequities. Towards eradicating existing racism in the field, we conclude with suggestions for researchers and leadership in professional psychological organizations.